การเยียวยาและฟื้นฟูจิตสังคมผู้ประสบภัยสงครามในพื้นที่ชายขอบ: บทวิเคราะห์เชิงรัฐศาสตร์และสังคมสงเคราะห์ - กันยาวรรณ, พิชิต (วารสาร มมร ยศสุนทรปริทรรศน์; Vol 2 No 2 (2025): วารสาร มมร ยศสุนทรปริทรรศน์-ปีที่ 2 ฉบับที่ 2 (พฤษภาคม-สิงหาคม 2568), 2025)
Armed conflicts affecting border areas have caused severe damage to human security, economic stability, social cohesion, and cultural integrity, with profound impacts on the psychological well-being and social relationships of affected populations. This article analyzes the psychosocial healing and rehabilitation processes for war-affected communities in border regions through the lens of political science and social work. The study employs the theoretical frameworks of Human Security, Human Rights, and Empowerment to guide the analysis. A qualitative research methodology was adopted, collecting data from war survivors, community leaders, local government officials, and NGOs through in-depth interviews and content analysis. The findings reveal that effective psychosocial recovery requires an integrated approach involving state mechanisms, local government organizations, and civil society, emphasizing the creation of safe spaces, the restoration of trust, and the provision of continuous psychosocial support services. The article recommends policy mechanisms that prioritize human rights, decentralize authority to enhance local government roles, and establish border-area psychosocial rehabilitation centers under multi-sectoral cooperation. Such measures are crucial for fostering long-term peace, resilience, and sustainable recovery in war-affected border communities.   Psychosocial healing, War-affected populations, Border areas, Political science, Social work